Transport and magnetic properties of Pb1-xMnxTe(Cr) Pb1-xMnxTe(Mo) - Artamkin, A. (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
We have investigated transport and magnetic properties of the Pb1-xMnxTe alloys doped with Cr and Mo. Anomalous behavior of the pinned Fermi level position with manganese concentration was observed. It was shown that in Pb1-xMnxTe(Mo) the Fermi level could be pinned within the valence band as well as within the gap. In the latter case considerable persistent photoconductivity was observed at low temperatures. The studies of the magnetic susceptibility showed that magnetic properties of Pb1-xMnxTe doped with Cr, Mo are defined by weak antiferromagnetic interaction between manganese ions.